2022
DOI: 10.1002/mren.202200042
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Downstream Contamination of Chemically Recycled Ethylene Feed Streams on the Kinetic Behavior of Ziegler‐Natta Catalysts and Microstructural Properties of HDPE and LLDPE

Abstract: The sustainability of consumer materials, such as plastics, belongs to the most important aspect of eco-efficiency analyses. Besides mechanical recycling, chemical recycling represents an interesting waste management pathway. In theory, this technique does not rely on single-grade feedstock to maintain product quality. However, cross-contamination of feedstocks potentially leads to above-specification impurities in obtained pyrolysis oils. This study investigates the potential downstream poisoning of a fourth-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 37 publications
1
5
0
Order By: Relevance
“…Thus, the differences in the incorporation behavior of the ZN catalyst for the various comonomers can be assigned to predefined active sites, and the correlation between MWD shift, comonomer content, and crystallinity can be extended by adding as a parameter the comonomer incorporation distribution, which allows a more detailed analysis. [12][13][14][15][16][17] The present work extends the knowledge on non-linear SCBs (Figure 1). Furthermore, the ability to characterize SCBs containing more than one CH 3 group using an IR detector (HT-SEC) is investigated.…”
Section: Introductionsupporting
confidence: 67%
See 2 more Smart Citations
“…Thus, the differences in the incorporation behavior of the ZN catalyst for the various comonomers can be assigned to predefined active sites, and the correlation between MWD shift, comonomer content, and crystallinity can be extended by adding as a parameter the comonomer incorporation distribution, which allows a more detailed analysis. [12][13][14][15][16][17] The present work extends the knowledge on non-linear SCBs (Figure 1). Furthermore, the ability to characterize SCBs containing more than one CH 3 group using an IR detector (HT-SEC) is investigated.…”
Section: Introductionsupporting
confidence: 67%
“…In this analysis, the M n values for five active centers were fixed based on the center point of the n ‐hexene LLDPE samples, and all further samples were evaluated based on the M n values fixed by this method. [ 16,17 ] We found that the percentage for Active Site 3 was higher for iso ‐hexene than for the n‐ hexene LLDPE samples. In contrast, neo ‐hexene LLDPE samples showed a higher percentage for Active Site 4.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…There are numerous studies involving the microstructure of HDPE and UHMWPE and their blends processed through different ways, as well as X-ray diffraction studies of HDPE or UHMWPE-containing polymers. ,, There have been studies on the evolution of microstructures in UHMWPE/HDPE blend fibers prepared by melt spinning, control of subinclusion microstructure in ternary blends consisting of HDPE, microstructural characterization of HDPE/polyamide blend through selective laser sintering processing, microstructural evaluation of HDPE along with its other properties after weathering, assessment of microstructure of HDPE post chemical recycling, post reinforcement for use as shielding materials against nuclear radiation, effect of various reinforcements on microstructure of UHMWPE consisting composites, , studies on microstructure of modified UHMWPE and UHMWPE consisting blend foams, and many more. Pandit et al investigated carbon-fiber-reinforced HDPE composites to improve printability of HDPE using FDM which otherwise show warping, shrinking, and weak bonding between HDPE and substrate .…”
Section: Introductionmentioning
confidence: 99%
“…Though it is a wellknown fact that these catalysts are sensitive to impurities, there are not many studies that quantified the impact of some common poisons on the catalyst activity for the latest supported Ziegler-Natta generations in gas phase polymerizations, nor investigated the consequences on the polymer microstructure and powder morphology, though such studies are currently of more interest due to the growing interest in monomers produced via chemical recycling of plastics which would contain more contaminants in comparison to conventionally produced monomers. [1][2][3] In this introduction, we will take a brief look at the few publications that have investigated the effects of poisons on propylene polymerizations experimentally and theoretically.…”
Section: Introductionmentioning
confidence: 99%